Analysis of family and school partnership in the teaching and learning process resignification (Research, Society and Development, 2017)
This essay objective thus, is to analyze the relation among family and school in the scientific literature and its implications to the learning and teaching process. It evokes the concern of the school agents, in the tangent to the creation of means to establish a significant relationship between the peers, in order to reestablish the appreciation of a systematized education for the socio-intellectual growth of the subject. Under the theoretical light of Evangelista, Gomes (2003), Parolin (2005), Petrine (2008), Cortella (2016) and other scholars of the theme, it seeks to analyze the barriers that hamper such partnership and, consequently, the low productivity in the scholar formation. This is a descriptive exploratory research with a qualitative approach that uses as data acquisition procedures a bibliographic study about the previous mentioned thematic. The bibliographic review indicates that the difficulty of interaction between family and school is due to several factors, among them the lack of critical awareness about different and related roles, as well as the interdependence of both for the development of the teaching and learning process. For various reasons parents and / or guardians do not fulfill their responsibility regarding the education of their children, a situation that causes frailty of ethical and moral values and in some cases, constitutes indiscipline at school.  The school, on the other hand, is overloaded and is not able to excel its true role. A worrisome reality that compromises the development of the individual in the society. In this context, the study of this issue requires priority in the ruling of discussions of the educational sphere, with views on the potentiality of these two important agents of transformation of the subject.